Corrosion and stray currents at urban track infrastructure - Katarina Vranešić; Stjepan Lakušić; Marijana Serdar (Građevinar, 2020)
Rails are a part of track structure where corrosion process inevitably occurs, except if they are fully insulated and devoid of contact with any other part of the structure (sleepers, fastening accessories) or electrolyte like moist soil or water in track structure. Corrosion occurs much faster in the presence of stray currents, which very soon results in the loss of material at the rail foot. The paper presents an overview and description of parameters influencing stray current levels, such as electrical potential in rail and longitudinal rail conductivity, rail-to-earth electrical resistance, electrical conductivity of load-bearing concrete layers of truck structure, and electrical conductivity of soil.